Public Debt and Economic Growth in the Balkan Countries - Kadia, Amarda (European Journal of Economics and Business Studies, 2020)
In order to empirically verify the impact of public debt on economic growth we have chosen an empirical model that is based on a conditional convergence equation that relates the GDP per capita growth rate to the level of income per capita and the savings as a percentage of the GDP. We are checking the non-linear impact of government debt on the economic growth of a country. We have chosen a sample of 9 Western Balkan countries, namely, Albania, Bosnia - Herzegovina, Bulgaria, Croatia, Macedonia, Montenegro, Romania, Serbia, Slovenia. We find that public debt has a negative effect on the economic growth, yet, this effect is dependent on the cost of debt. If the debt is used to create jobs that will eventually stimulate consumption, then the capital repayment and the interest costs will most probably not jeopardize the economic situation or increase the taxes to repay the debt. Additionally, if the growth of the real interest rate of debt is higher than the real GDP growth, this will lead to the increase of the debt/GDP ratio.